Fructans and other water soluble carbohydrates in vegetative organs and fruits of different Musa spp. accessions - Cruz-Cárdenas, Carlos I.; Miranda-Ham, María L.; Castro-Concha, Lizbeth A.; Ku-Cauich, José R.; Vergauwen, Rudy; Reijnders, Timmy; Van den Ende, Wim; Escobedo-GraciaMedrano, Rosa M. (Frontiers in Plant Science, 2015)
The water-soluble carbohydrates (WSC) glucose, fructose and sucrose are well-known to the great public, but fructan represents another type of WSC that deserves more attention given their prebiotic and immunomodulatory properties in the food context. Although the occurrence of inulin-type fructo-oligosaccharides (FOS) was proposed in the fruit of some banana accessions, little or no information is available neither on the exact identity of the fructan species, nor on the fructan content in different parts of banana plants and among a broader array of banana cultivars. Here, we investigated the WSC composition in leaves, pulp of ripe fruits and rhizomes from mature banana plants of eleven accessions (I to XI), including both cultivated varieties and wild Musa species. High performance anion exchange chromatography with integrated pulsed amperometric detection (HPAEC-IPAD) showed the presence of 1-kestotriose [GF2], inulobiose [F2], inulotriose [F3], 6-kestotriose and 6G-kestotriose (neokestose) fructan species in the pulp of mature fruits of different accessions, but the absence of 1,1-nystose and 1,1,1 kestopentaose and higher degree of polymerization (DP) inulin-type fructans. This fructan fingerprint points at the presence of one or more invertases that are able to use fructose and sucrose as alternative acceptor substrates. Quantification of glucose, fructose, sucrose and 1-kestotriose and principal component analysis (PCA) identified related banana groups, based on their specific WSC profiles. These data provide new insights in the biochemical diversity of wild and cultivated bananas, and shed light on potential roles that fructans may fulfil across species, during plant development and adaptation to changing environments. Furthermore, the promiscuous behavior of banana fruit invertases (sucrose and fructose as acceptor substrates besides water) provides a new avenue to boost future work on structure-function relationships on these enzymes, potentially leading t